Of wolves and people – How people’s relationship with nature affects wolf conservation in Portugal - Fernandes Martins,Adriana (Master Thesis Series in Environmental Studies and Sustainability Science, 2023)
Biodiversity conservation is a key environmental issue. Large carnivores face conservation challenges due to their predatory nature, generating human-wildlife conflicts. For the Iberian wolf to survive in Portugal, human-wolf conflicts must be identified, addressed, and mitigated. Investigating the social dimensions of these conflicts is crucial to reach solutions. Through a literature review and interviews with stakeholders, I identify the underlying problems and possible solutions to mitigate human-wolf conflicts through a multiple environmentalities perspective. Then, I investigate what undermines conflict resolution using the concept of human dimensions. I find that wolf depredation is the main source of conflict. Possible solutions include damage compensation schemes and ecological restoration. While these are known to researchers and policymakers, stakeholder conflict and political inaction have hampered progress. Based on the results, I suggest integrating human dimensions as an alternative to traditional top-down approaches to ease tensions among stakeholders, something crucial to mitigating human-wolf conflicts.
Keywords: wolf conservation; human-wolf conflicts; stakeholder conflict; human dimensions; sustainability science